2012
DOI: 10.1089/gtmb.2011.0370
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-Being and Family Satisfaction Levels Five Years After Being Confirmed as a Carrier of the Machado-Joseph Disease Mutation

Abstract: The present study on long-term outcome of presymptomatic testing for Machado-Joseph disease (MJD) aimed to evaluate the psychological well-being and the familial satisfaction of subjects that 5 years prior received an unfavorable result in the predictive testing (PT). The study included 47 testees of Azorean origin (23 from the island of Flores and 24 from S. Miguel) that completed the fourth evaluation session of the MJD protocol, and undertook a neurological examination at the moment of participation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 15 publications
1
18
1
Order By: Relevance
“…This hypothesis should be further investigated. Anxiety and depression related to genetic testing have been reported in subjects at risk for hereditary, late-onset neurological disease, namely in Huntington and Machado-Joseph diseases (Gonzalez et al 2004(Gonzalez et al , 2012Tibben 2007;Timman et al 2004;van der Meer et al 2015). Similar results were found in TTR-FAP at-risk subjects who looked for and did genetic testing (Ledo et al 2016;Lêdo et al 2016;Paneque et al 2009;Rolim et al 2006).…”
Section: Discussionsupporting
confidence: 60%
“…This hypothesis should be further investigated. Anxiety and depression related to genetic testing have been reported in subjects at risk for hereditary, late-onset neurological disease, namely in Huntington and Machado-Joseph diseases (Gonzalez et al 2004(Gonzalez et al , 2012Tibben 2007;Timman et al 2004;van der Meer et al 2015). Similar results were found in TTR-FAP at-risk subjects who looked for and did genetic testing (Ledo et al 2016;Lêdo et al 2016;Paneque et al 2009;Rolim et al 2006).…”
Section: Discussionsupporting
confidence: 60%
“…[7][8][9][10]13,14 Although most report on short-term results of PST, some literature already presents long-term psychosocial impacts of HD predictive testing. 3,11,[14][15][16][17][18][19] Two very specific Portuguese diseases, MJD and FAP, also follow a severe neurodegenerative pathway and remain until now without an effective treatment or cure. For MJD, it is important to highlight the frequency of cerebellar ataxia, progressive external ophthalmoplegia, and pyramidal signs.…”
Section: Introductionmentioning
confidence: 99%
“…7,13,[30][31][32][33] Those studies have generally shown a decrease in anxiety scores from the pre-test to the post-test evaluation. 2,13 The few midand long-term studies available suggest that, in general, there is an absence of negative impact after some years, 11,16,19 specifically in relation to anxiety levels. The study by Decruyenaere et al 15 indicates a decrease in the score for anxiety in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…There are fewer studies on PST for MJD and other SCAs than for HD; these studies mainly encompass the Portuguese, Cuban, French and Brazilian experiences (Paúl et al , 1999; Lima et al , 2001; Goizet et al , 2002; Gonzalez et al , 2004; Rolim et al , 2006a,b; Cecchin et al , 2007; Paneque et al , 2007a,b, 2009; Gonzalez et al , 2012; Cruz-Mariño et al , 2013; Guimarães et al , 2013) (Paiva RSR, 2006, PhD thesis, UNICAMP, Campinas). We hope this report will encourage similar studies in other populations, mainly in Latin America.…”
Section: Discussionmentioning
confidence: 99%